Planning for Tomorrow's Population - Dow Chemical Company (1951)
Color print advertisement for Dow Chemical Company. The advertisement features an illustration of several men in suits consulting a large overhead map of a city. The accompanying text describes the role of Dow Chemical products in "the city of tomorrow," including Dowflake (calcium chloride), as well as other chemicals used for sanitation, waste disposal and construction. This advertisement appeared in The Saturday Evening Post.
Keywords: Advertising; Dow Chemical Company; Chemical industry; Corporations; Civil engineering; City planning; Advertising, Industrial